Synthesis of biodegradable lubricant from jatropha oil with high content of free fatty acids. - Gunam Resul, Mohamad Faiz Mukhtar; Mohd. Ghazi, Tinia Idaty; Muhammad Syam, Azhari; Idris, Azni (2008)
Plant oil extracted from a non edible plant has the potential application as biodegradable lubricant. Such plant as toxic contained Jatropha curcas inhibits human consumption and thus making it suitable for such application since it does not compete with the food production. However, high content of free fatty acids (FFA) in the jatropha oil (triglycerides) is found to have significant effect in the production of bio-lubricant. The formation of fatty acids occurs when the triglycerides are hydrolysed with moisture due to poor storage and handling. This paper discusses the techniques performed to produce high yield of bio-lubricant from jatropha oil containing high content of FFA up to 30%. It is reported that more than 80% yield of jatropha bio-lubricant was successfully achieved. Lubricity characteristics such as the pour point, viscosity and thermal oxidative stability for the produced jatropha bio-lubricant are found to be comparable with the other vegetable oil based lubricants.